Faktor - Faktor yang Mempengaruhi Strategi Penyuluhan di Era Pandemi Terhadap Minat Pemuda dalam Usahatani Brokoli Organik Desa Sumberejo, Kecamatan Batu, Kota Batu - Simo, Daniel; Noywuli, Nicolaus; Keruru, Maria Nesti; Merna, Diana (Jurnal Kridatama Sains dan Teknologi, 2025)
A well-thought-out and flexible extension plan is crucial to promoting higher small-scale farmers' incomes. Farmers may boost agricultural output and compete in a larger market by using an appropriate extension strategy. Finding the key elements influencing young people's interest in growing organic broccoli in Sumberejo Village, Batu District, is the goal of this research. Knowledge, experience, and information are among these elements, which are often divided into two categories: internal factors (such intrinsic qualities) and external ones (like social environment, education, and familial influence). Sumberejo Village was selected due to its excellent potential for growing broccoli and Batu City's favourable soil conditions. The analytical technique known as structural equation modelling, or SEM, enables the testing of causal links between variables in the study model. The Cronbach's Alpha coefficient reliability test findings indicated that all items were valued at ≥ 0.6, suggesting that the research instrument was deemed practicable and trustworthy. To gather research data, the questionnaire was subsequently given to 60 responders